The Potency of Cinnamomum Zeylanicum to Prevent Diseases: A Review - Casey Christiany; Susana Elya Sudrajat; Ika Rahayu (Eureka Herba Indonesia, 2021)
Plants are an important source of traditional medicines that can be used to improve health. Cinnamon (Cinnamomum zeylanicum) has long been recognized to have many benefits. Cinnamon was used traditionally as a remedy for arthritis, diarrhea, allergies, and ulcers. This literature review aimed to identify the bioactive compounds and bioactivity of cinnamon. Literature searches used PubMed and Google Scholar. A total of 55 full-text articles met the inclusion criteria of the review. The extract or essential oil of cinnamon contains many bioactive compounds, such as eugenol, cinnamic acid, linalool, β-caryophyllene, coumarin, and trans cinnamyl acetate, and 1.8 cineole. These compounds have several bioactivities including anti-cancer, anti-arrhythmia, anti-inflammatory, anti-diabetic, anti-atherosclerosis, anti-cholinesterase, and anti-lipid oxidation. Cinnamon extract has excellent potential as an antioxidant and antidiabetic agent. Its potential and unique taste have contributed to its wide use in herbal remedies.